What are the perceptions of intensive care staff about their sedation practices when caring for a mechanically ventilated patient?: A systematic mixed-methods review - Sarah Varga; Tony Ryan; Tracey Moore; Jane Seymour (Elsevier, 2022)
Background: Sedation is used alongside mechanical ventilation for patients in intensive care units internationally; its use is complex and multifaceted. Existing evidence shows that the ways health care professionals use sedation significantly impacts patient outcomes, including how long someone spends on a ventilator, length of stay in intensive care and recovery. Objective: Our study aimed to systematically review and synthesize qualitative and quantitative evidence about how intensive care staff perceive sedation practices when looking after sedated and mechanically ventilated patients. Design: We performed a systematic integrated mixed-methods literature review collecting qualitative and quantitative studies according to inclusion and exclusion criteria. Studies were included if they were published from 2009 and focused on perceptions of staff working in general adult intensive care units and caring for mechanically ventilated patients. Setting(s): General adult intensive care units. Participants: Health care professionals working in adult intensive care units. Methods: Screening, data extraction and quality appraisal was undertaken by SV. Screening for inclusion and quality issues were reviewed by TR, TM and JS. The following databases: Embase, BNI, PubMed, Scopus, AMED, CINAHL, ASSIA, The Cochrane Library and Google Scholar. We used an assessment tool called the Mixed Methods Appraisal Tool. The studies were assessed and analysed by transforming the qualitative and quantitative data into 'text-in-context' statements. The statements were then synthesized using thematic analysis. Results: Eighteen studies were included from ten countries, fourteen quantitative and four qualitative. Three overarching themes were identified: 'Variation in Decision Making', 'Challenges in Decision Making' and 'Thinking Outside the Box'. Existing studies revealed that there is considerable variation in most aspects of perceived sedation practice. Staff face challenges with interprofessional collaboration and sedation practice, and there are barriers to using sedation protocols and light sedation. There is also evidence that there is a need for health care professionals to develop coping strategies to help them facilitate lighter sedation. Conclusions: A review of a decade of evidence shows that variation in decision making and challenges in decision making should be addressed to improve the care of the sedated and ventilated patient, and improve the caregiving experience for staff. Staff continue to require support with sedation practice, especially in light sedation. Research should now focus on how to help staff cope with looking after lightly sedated patients. In addition, future studies should focus on exploring sedation practices using qualitative methods as there is a dearth of qualitative evidence. Tweetable abstract: Staff perceive a range of complex challenges that explain some of the variability in sedation practice for the ventilated patient in ICU.